2012
DOI: 10.1063/1.4763458
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of microwaves through exchange-coupled bi-layer magnetic films in ferromagnetic and standing spin wave resonances

Abstract: In this work, we have studied theoretically the transmission and reflection of electromagnetic waves in the microwave frequency range through the in-plane magnetized exchange-coupled bi-layer ferromagnetic metallic films. It was found that responses of the films in transmission and reflection are very different. In transmission, the response of the fundamental mode dominates, but in reflection, the first exchange mode demonstrates the largest variation in amplitude with respect to the off-resonance regime. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Substitution of Eqs. (13,14) into Eq. (16) allows one to eliminate the unknown integration constant B…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of Eqs. (13,14) into Eq. (16) allows one to eliminate the unknown integration constant B…”
Section: Numerical Modelmentioning
confidence: 99%
“…The microwave conductivity contribution to the stripline broadband ferromagnetic resonance (FMR) response of highly-conducting (metallic) magnetic multilayers and nanostructures of sub-skin-depth thicknesses has attracted significant attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It has been shown that these effects are important when the microwave magnetic field is incident on only one of the two surfaces of a planar metallic material (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this study was carried out for partial pressures well above 1 atmosphere (1.3-5.2 atm). The works [28,29] reported a decrease in PMA on hydrogen absorption. Methods which are very impractical for sensor applicationsvibrating sample magnetometry and polarized neutron reflectivity -were utilized in these works.…”
mentioning
confidence: 99%
“…An extremely low amplitude microwave field can penetrate an electrically insulating wall and probe the sensor through the wall. More importantly, because the sensor is made from metallic conductors, the sensor itself serves as a perfect shield for microwaves [27][28], not allowing the microwave power to penetrate into the vessel that potentially contains the hydrogen gas. Thus, there will be no electrical fields capable ignite the gas present inside the vessel.…”
mentioning
confidence: 99%
“…It takes a couple of more seconds to convert the obtained Z r values into S21 by using Eqs. (18)(19)(20)(21)(22)(23)(24)(25) from [16].…”
Section: Theorymentioning
confidence: 99%